PERAN LPTK DALAM MENYIAPAKAN GURU PAI PROFESIONAL - Rojak, Abdul; Hasbiyallah, Hasbiyallah (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2021)
Quality education is influenced by several factors, including teachers, the learning process, infrastructure, curriculum, and school management. In this case, the teacher is the main key to the quality of education. Professional teachers are a determining factor for the success of education in schools because teachers are the central and source of teaching and learning activities. The Educational Personnel Education Institute (LPTK) is the only place to produce teachers who have high-level skills and grades as professional educators. This article aims to determine the role of the LPTK in preparing professional educators. This article is also expected to contribute to the study of increasing teacher professionalism. The approach used in this research is a qualitative approach with library research methods. Research results from various references indicate that the LPTKs should start to improve, innovate more and restructure so that they can produce professional and more competent educators in their fields.